Analysis of Public Service Quality for Waiting Room Facilities at Yogyakarta International Airport - Mariana Tari; Kifni Yudianto (CV. Rayyan Dwi Bharata, 2023)
The purpose of this study is to explain that the waiting room infrastructure at Yogyakarta International Airport is able to facilitate the needs of passengers while in the airport ground area. In addition, facilities that accommodate the needs of passengers are able to create an impression of good feedback so that the airport can improve the quality of airport services. Apart from that, it is also useful with the impact of the spread of economic activities that can be influenced by the existence of Kulon Progo which is close to Glagah Beach, this triggers ecotourism and introduces tourism that is close to Yogyakarta International Uda Airport. The availability of transportation facilities and infrastructure also adds to the primary network of the economy. This study uses a qualitative method. Data collection techniques used to find data by using a system or method of interviews, observation and documentation. Public services and airport facilities are one unit in achieving passenger satisfaction in the airport area. With a building structure that is typical of Yogyakarta custom, therefore it can be a characteristic of Yogyakarta's cultural diversity, becoming iconic or the center of attention for souvenirs. The results of the research are based on the results of interviews and observations of objects that have a positive impression or the Yogyakarta International Airport facilities really support operational activities in the waiting room. In addition, the results of the observations that the researchers made were that the waiting room facilities had good availability and infrastructure.